Mengembangkan Potensi Anak Melalui Seni dalam Lomba Mewarnai untuk Meningkatkan Pemahaman Sosial dan Budaya di Jl. Binalatung RT 11, Pantai Amal Baru, Tarakan Timur - Nurul Hidayat; Suci Wulandari; M. Faldi Kurniawan; Sofya Yuliana B.; Hilda, Hilda; Lia Bayu Natasha; Rio, Rio (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This community service project aims to develop children's potential through the art of coloring as an effective educational tool to enhance social and cultural understanding. The activity was held at Jl. Binalatung, RT 11, Pantai Amal, Tarakan Timur, a coastal area that is also a border region. The background for this project is the limited access of children in this area to creative activities that could support their personal development and awareness of social and cultural diversity. A coloring competition was chosen as the approach, involving 30 participants from kindergarten to elementary school age, many of whom do not continue to formal education.Using a participatory method, children were not only invited to color but were also given an understanding of the meanings and cultural values embedded in each image. Furthermore, the activity was designed to foster a sense of togetherness, sportsmanship, and self-confidence. The results showed very high enthusiasm from the participants. They were not only able to produce beautiful artworks but also demonstrated an increased understanding of the importance of appreciating differences and cultural diversity. This report proves that the art of coloring plays a crucial role as a tool to bridge the knowledge gap and foster cultural awareness, especially for children in remote and border areas who have limited access to education and educational entertainment. Therefore, it is recommended that similar programs be continued with more varied materials to support the holistic development of children in coastal regions.